2018
DOI: 10.1145/3274436
|View full text |Cite
|
Sign up to set email alerts
|

"It's Kind of Boring Looking at Just the Face"

Abstract: Mobile videochat use has been growing, especially for teens. To better understand teens' videochat practices, we conducted a two-week photo diary study with 16 teens. We found that most often, teens videochat with their closest friends from their bedrooms when they feel lonely or bored. Teens turned to videochat when understimulated but also felt understimulated during videochat. In order to manage this, they multitasked -teens moved from active chatting to co-presence while engaged in separate activities like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…in pubs [47], and further quantified by Mayer et al [40]. Similarly to findings in the context of videochat [59], lack of reciprocity of attention between our participants was highlighted as a potential source of conflicts. Others have identified the phenomenon where people desire technology non-use [4,53], wishing to dis-integrate the smartphone from everyday life [25].…”
Section: Reflections Vs Prior Worksupporting
confidence: 79%
“…in pubs [47], and further quantified by Mayer et al [40]. Similarly to findings in the context of videochat [59], lack of reciprocity of attention between our participants was highlighted as a potential source of conflicts. Others have identified the phenomenon where people desire technology non-use [4,53], wishing to dis-integrate the smartphone from everyday life [25].…”
Section: Reflections Vs Prior Worksupporting
confidence: 79%
“…(P38) This behaviour of creating an 'open channel' has been noted in other studies of video-mediated communication [31,60]. For the problem of homesickness, having an open channel may help to recreate the type of conversational flow that exists in the home, where people do not need to attend to each other but can remain in conversation or focus on other activities [60]. An additional and perhaps more interesting outcome of establishing an open channel was the idea that the channel could prevent loneliness while providing a sense of awareness about happenings at the remote site, especially with respect to ambient sounds.…”
Section: Building Social Co-presence To Recreate the Homesupporting
confidence: 56%
“…It feels nice. " (P38) This behaviour of creating an 'open channel' has been noted in other studies of video-mediated communication [31,60]. For the problem of homesickness, having an open channel may help to recreate the type of conversational flow that exists in the home, where people do not need to attend to each other but can remain in conversation or focus on other activities [60].…”
Section: Building Social Co-presence To Recreate the Homementioning
confidence: 81%
“…While multitasking during one's own work mostly impacts personal productivity, special consideration of multitasking during meetings is warranted, as this can additionally impact other colleagues and their productivity [31]. Past work has looked at how people engage in multitasking both during in-person meetings and presentations [6,30,31], as well as online collaborative activities, such as remote meetings leveraging subjective feedback or perceptions [45,62]. For example, in educational settings, the use of laptops during a lecture has been shown to have a negative impact on attention, where students tend to engage in activities such as web-surfng or emailing rather than activities related to the lecture [6,30].…”
Section: Multitasking During Meetingsmentioning
confidence: 99%
“…. Prior work has investigated how people engage in multitasking during collaborative activities such as meetings and video chats, both in-person and online [30,31,45,62]. However, these works are mainly based on small-scale qualitative studies, and to the best of our knowledge, no research to date has reported systematic and comprehensive evidence from large populations.…”
mentioning
confidence: 99%